Attitudes Toward Asylum Policy in a Divided Europe: Diverging Contexts, Diverging Attitudes? - Van Hootegem, Arno; Meuleman, Bart; Abts, Koen (Frontiers in Sociology, 2020)
The large inflow of asylum-seekers in recent years has intensified divides between European states that have introduced restrictive asylum procedures and nations that have adopted more open policies. Although a growing body of research has addressed these opposing approaches and their implications for the European integration project, insight into the social basis of these restrictive or open asylum policies remains underdeveloped. Hence, the current study provides detailed insight into public preferences for asylum policies and offers a new understanding of how these attitudes are affected by diverging socio-economic realities across Europe. In addition, this paper considers the role of individual factors that coincide with publicly adopted frames in contemporary asylum debates. In particular, to explain how contextual differences reflect on opinion climates, the impacts of the policy, economic and migratory context are studied. On the individual-level, we focus on threat perception and human values, which represent humanitarian, economic and cultural frames. To explore these relations, data on 20 countries from the European Social Survey Round 8 (2016) are analyzed through a multilevel structural equation modelling approach. Results indicate that, on the contextual-level, only unemployment rates have a significant impact and, rather surprisingly, lower unemployment rates provoke a more negative opinion climate. Yet, this relationship seems to be largely driven by some specific countries that are characterized by large unemployment rates and relatively positive opinion climates simultaneously. The migratory and policy context, on the other hand, do not influence attitudes towards asylum policy. This indicates that it are not necessarily the countries facing the largest inflow of asylum-seekers or issuing the most positive decisions on asylum applications that have the most restrictive opinion climates. As shown by the important roles of human values and threat perceptions, which represent widely adopted frames, public discourses seem much more important in explaining attitudes towards asylum policy across Europe.